Analisis Strategi Promosi Berimbang dalam Mempertahankan Kuantitas Siswa di MAN IC Pasuruan dan MANPK Jombang - Afifah, Faiqotul; Maarif, Samsul; Sahudi, Sahudi (Jurnal Pendidikan Madrasah, 2024)
This study aims to analyse the educational marketing strategies of MANPK Jombang and MAN Insan Cendekia Pasuruan in addressing the challenges of increasing competition in the education sector. This research employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. A SWOT analysis was conducted to evaluate the strengths, weaknesses, opportunities, and threats of both institutions. The findings reveal that MANPK Jombang emphasizes Islamic-based education, while MAN Insan Cendekia Pasuruan highlights science and technology-oriented education. Despite their different approaches, both institutions face challenges in technological adaptation and optimizing digital marketing strategies. This study concludes that implementing innovative digital marketing strategies, such as utilizing social media, interactive websites, and virtual tours, is crucial to enhancing competitiveness and attractiveness. Recommendations are provided to strengthen digital promotion to expand student enrolment outreach.